The Measurement of Legitimacy: a Rush to Judgment? - Cao, Liqun (Asian journal of criminology, 2019)
In an important article on the methodological issues surrounding measuring of police legitimacy, Jackson and Bradford (Asian Journal of Criminology,https://doi.org/10.1007/s11417-019-09289-w, 2019) adequately warn against the use of confirmatory factor analysis as an adjudication tool for differentiating the possible sources and constituent components of police legitimacy. However, in the process of arguing against the Sun et al.’s (Asian Journal of Criminology, 13, 275-291, 2018) measure of legitimacy, they inadvertently bring attention to a more foundational issue—How should scientists conduct research and test theories in various cultures? Furthermore, their argument against the alternative measuring of police legitimacy elucidates an extensive problem facing criminology—they have brought attention paid to the interrogation of operationalizing key constructs within criminology. We argue that Jackson and Bradford’s (2019) critiques of Sun et al.’s (2018) modeling and subsequent testing of police legitimacy in China are a bit overstated. Additionally, we contend that testing theories, such as police legitimacy, across cultures should be conducted both top-down and bottom-up—neither are necessarily contradictory. We urge readers to be the ultimate amicus curiae because this issue is not a concretely right-or-wrong type issue.